Kajian mengenai faktor-faktor yang mempengaruhi ketidakhadiran kerja dan corak ketidakhadiran di Syarikat CMS Cement Sdn. Bhd. - Woo, Sook Han (Universiti Malaysia Sarawak (UNIMAS), 1997)
Absenteeism occurs when someone fails to turn up for work when he/she is suppose to. It is a global problem plaguing most of the nations and organisations of the contemporary society. Absenteeism imposes costs, directly or indirectly. on the absentee, other co-workers, the organisation and the nation as a whole. Thus, it is crucial that the causes of absenteeism should first be studied and determined before any meaningful effort to combat absenteeism can be effectively implemented. Thus, this study seeks to study or determine the factors which may influence an individual decision to absent from work Besides, it also seeks to explore the pattern of absenteeism Datas obtained from the CMS Cement Sdn. Bhd are analysed using the SPSS program statistical analysis by frequency, Spearman correlation and cross-tabulation. indicate that (I) age. tenure. marital status and salary are significantly associated with absenteeism: while (2) job satisfaction and Transporation problem are not significantly associated with absenteeism Thus, this study provides partial support for Steers and Rhodes process model of work absenteeism and the Equity Theory. The present study also reveals that absenteeism rale is higher during seasonal festival